The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019 Fourteenth International Conference on Ecological Vehicles and Renewable Energies (EVER) 2019
DOI: 10.1109/ever.2019.8813580
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Optimal Sizing of Photovoltaic Water Pumping Systems – Sensitivity Analysis

Abstract: Recently we have developed a model of photovoltaic water pumping systems (PVWPS) for domestic water access in poor rural areas. In this article, we perform a sensitivity analysis over the 14 parameters of this model. We study how the variation of the parameters value influences the model output and the optimal sizing obtained from the model, for both the dry and the wet season. Results indicate that the peak power of the photovoltaic modules, the efficiency of the motor-pump and the tank volume have the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…In this article, only the source and the temporal resolution of change (see section III) while we use measured data with a 1 minute temporal resolution for the two other inputs of the model ( and ). Indeed, we showed that has a small effect on the model output [12] and we investigated the influence of in a previous article [13].…”
Section: Photovoltaic Water Pumping System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this article, only the source and the temporal resolution of change (see section III) while we use measured data with a 1 minute temporal resolution for the two other inputs of the model ( and ). Indeed, we showed that has a small effect on the model output [12] and we investigated the influence of in a previous article [13].…”
Section: Photovoltaic Water Pumping System Modelmentioning
confidence: 99%
“…The data were rescaled to an evenly spaced temporal resolution of 1 minute by nearest interpolation. The evolution of the measured quantities has been reported in [10] and [12].…”
Section: Photovoltaic Water Pumping System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a suitability map is produced for solar PV-suitable sites. The criteria weights were changed with a certain percent from that of original weights to show the change in the suitability map of solar PV [30,[48][49][50][51][52][53].…”
Section: Sensitivity Analysis Concepts In Arcgismentioning
confidence: 99%
“…While focus on the level of static water not accounting for costs of (drilling for wells, exploration and manpower) were not considered in [14]. The authors in [15], performed sensitivity analysis on 14 parameters and showed that the thermal parameters and hydraulic losses had a negligible effect on the model output and the optimal formation. In [16] the effect of temporal resolution of water consumption rate on model accuracy and optimum sizing (pv sys) was studied.…”
Section: Introductionmentioning
confidence: 99%